1,4-Diazabicyclo[2.2.2]octane-Catalyzed Multicomponent Domino Strategy for the Synthesis of Tetrasubstituted NH-Pyrroles - Chang, Xiangqing; Yang, Xiaofeng; Chen, Zhiwei; Zhong, Weihui (Synlett, 2019)
A mild and efficient 1,4-diazabicyclo[2.2.2]octane (DABCO)-catalyzed three-component domino reaction was developed for the synthesis of highly functionalized NH-pyrroles from arylglyoxal monohydrates, enamino esters, and cyclic 1,3-dicarbonyl compounds in 1,4-dioxane at room temperature for 0.5 hours. Various substituted NH-pyrroles were obtained in moderate to good yields.
Keywords: multicomponent reaction; pyrroles; DABCO; cyclization; arylglyoxal monohydrates; enamino esters